A new species of Zographetus Watson, 1893 (Lepidoptera: Hesperiidae) from Sikkim, eastern Himalaya, India - Karmakar, Tarun; Lepcha, Sonam Wangchuk; Basu, Dipendra Nath; Kunte, Krushnamegh (Zootaxa, 2021)
A new species, Zographetus dzonguensis sp. nov., is described based on three male specimens from Upper Dzongu, North Sikkim District, Sikkim, India. The new species is closely similar to Z. pangi from Guangdong and Z. hainanensis from Hainan, China, from which it is distinguished based on the following combination of external characters: (a) forewing with the white spot at the base of space M3 being sharply pointed at the inner edge and conspicuously more elongated, and (b) on underside of hindwing, all chocolate-brown spots being smaller, in Z. dzonguensis sp. nov. compared with both Z. pangi and Z. hainanensis. In Z. dzonguensis sp. nov., the male genitalia may be distinguished as follows: (c) tegumen and uncus are almost equal in length, (d) the dorsal outline of tegumen is relatively flat, and (e) saccus is distinctly bent upward as angle between vinculum and saccus is more acute than in Z. pangi and Z. hainanensis.